Reduction of external rail wearing on road curves - Povilaitiene, Inesa; Laurinavičius, Alfredas (Journal of Civil Engineering and Management, 2004)
Railway line curves restrict train speed. Besides, there is a high side wearing intensity in the external rail head on the curves. The main functions of cant are discussed in the article. Results of experimental research which was carried out in order to estimate the influence of cant and gauge increase on the curves of rail head side wearing intensity, are presented. Improved cant calculation methodology, which assures rail head side wearing intensity reduction and safe railway traffic, is suggested.First Published Online: 14 Oct 2010